The Relationship between Military Training Content, Willingness to Learn and Execute Defence and Security Jobs - Ismail, Azman; Mat Deli, Mazzlida; Mohd Zainol, Noor Azmi; Nik Abdullah, Nik Anis Sazwani; Abdul Ghani Azmi, Ilhaamie (UI Scholars Hub, 2025)
Research Aims: The study evaluates the mediating role of trainees’ willingness to learn in the relationship between military training content and trainees’ willingness to execute defence and security jobs. Design/Methodology/Approach: A survey method was conducted using a cross-sectional research design to gather 343 self-report questionnaires from Malaysian army personnel. A purposive sampling technique was utilised while the SmartPLS was employed to assess the measurement model and test the structural equation model. Research Findings: The findings of a structural equation modelling test confirmed that the trainees’ willingness to learn is an important mediating variable between military training content and trainees’ willingness to execute defence and security jobs. Theoretical Contribution/Originality: This study reveals that the relationship between military training content and trainees’ willingness to execute defence and security jobs is mediated by the trainees’ willingness to learn. This finding has supported and broadened past studies in Southeast Asia and other countries. Managerial Implication in the South East Asian Context: The findings assist the human resources department in understanding the diverse perspectives regarding the willingness to learn and formulate employee development programs to maintain and enhance the performance of military organisations amid the evolving global defence and security landscape. Research Limitation & Implications: The data were collected from military organisations in a developing country. Thus, this investigation may have an impact on how broadly the results may be applied. Future studies should consider more varied samples.